Good governance for sustainable blue economy in small islands: Lessons learned from the Seychelles experience - Benzaken, Dominique; Voyer, Michelle; Pouponneau, Angelique; Hanich, Quentin (Frontiers in Political Science, 2022)
The blue economy has emerged as an influential global concept. It is commonly understood to relate to the development of the ocean in a manner which also addresses concerns about ocean health in the face of increasing demands on ocean resources, marine pollution, and climate change. While the blue economy holds potential to act as an integrating policy framework for the sustainable development of the ocean, to date, there are limited examples of implementation in practice to test the usefulness of the concept. Based on a typology of “good governance” adapted from existing global typologies, we investigated the role of blue economy governance in enabling integration. We used a mixed methods approach to explore the experience of Seychelles, a blue economy early adopter, combining policy and institutional analysis, semistructured interviews with key actors and partners, and country fieldwork. Our analysis shows that from its inception, Seychelles' vision of blue economy was a transformative model of development based on the protection and sustainable use of ocean resources for the benefit of Seychellois, consistent with the SDGs. Thanks to early political leadership and international engagement, the adoption of the blue economy concept was successful in raising awareness of the ocean health and its connection to people and the economy, and in establishing the basis of a national blue economy “architecture,” which helped secure innovative finance for implementation. Transitioning to implementation, several governance challenges emerged, which included maintaining high-level political momentum, stakeholder engagement, and institutional coordination and capacity. While some governance barriers to effective integration may be unique to Seychelles, some are common to SIDS, and others are found in a range of governance settings. Seychelles international visibility has brought high expectations, not always commensurate with local aspirations, capabilities, and jurisdictional responsibilities. Bridging the gap between global expectations and local realities will require support for locally driven institutional reforms, which take account of issues of scale, culture, and capacity.